2022
DOI: 10.3390/children9020260
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Mobile Health Solution to Facilitate the Transition from NICU to Home: A Qualitative Study

Abstract: There is limited information about caregiver and provider perspectives regarding the design of a mobile health solution to facilitate the transition from the neonatal intensive care unit (NICU) to home. Focus groups were conducted with English- or Spanish-speaking families enrolled in an urban high-risk infant follow-up clinic and with their care providers. We generated salient themes using an inductive thematic analysis. Twenty-two participants completed the study. Among caregivers, the infant’s median gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…Although there is less evidence available on the impact of post-NICU discharge support and education interventions, multiple benefits for parents (e.g., increased competency and confidence) have been demonstrated (Griffith et al, 2022). As with parents in other studies, parents proposed improved engagement with community-based providers and services (Page et al, 2020;Lakshmanan et al, 2022). The strategies the parents proposed to improve their preparedness, confidence, and capability were based on their experiences and are ones that are relatively simple to implement.…”
Section: Discussionmentioning
confidence: 96%
“…Although there is less evidence available on the impact of post-NICU discharge support and education interventions, multiple benefits for parents (e.g., increased competency and confidence) have been demonstrated (Griffith et al, 2022). As with parents in other studies, parents proposed improved engagement with community-based providers and services (Page et al, 2020;Lakshmanan et al, 2022). The strategies the parents proposed to improve their preparedness, confidence, and capability were based on their experiences and are ones that are relatively simple to implement.…”
Section: Discussionmentioning
confidence: 96%
“…These articles outlined and described a unique approach to this process in detail. For example, Lakshmanan et al is a qualitative prospective study in which study participants were interviewed in focus groups about desired components of a mobile app for parental support during transition from NICU to home ( 21 ). A unique feature of this study was the inclusion of both parents (eleven participants total) and providers (eleven participants total) with the aim of gaining insights from both relevant stakeholders.…”
Section: Narrative Reviewmentioning
confidence: 99%
“…The use of eHealth expanded radically during the COVID-19 pandemic [9], but various barriers remain before integration into pediatric clinical practice is completely successful [10][11][12][13]. Studies have reported that the use of eHealth in pediatric clinical care can bridge the transition from hospital to home and increase interaction between the two by efficiently and conveniently providing information and communication [14][15][16], which helps promote confident self-management among parents in caring for children with various medical needs at home [2,[15][16][17], improve symptom control in the child, and reduce parental worries and insecurity [2,[18][19][20][21][22]. However, eHealth interventions for families of children living with health conditions and the evidence of eHealth in pediatric clinical practice are still limited [23][24][25].…”
Section: Introductionmentioning
confidence: 99%